Peasant Farming, A Buffer for Human Societies. Issue 2 (June 2015) - Hilmi, Angela; Burbi, Sara
Abstract This article explores the importance of peasant farming worldwide, the debate about its disappearance and the way it is being impacted by differentiated policies. It takes two examples, Tunisia and Egypt, during post-colonial times. In both cases policies tended to favour the modernization of agriculture, ignoring the contribution of peasant farming to the national economies. But interestingly the data show a surprisingly significant importance and increase in the number of small farms in both countries. While theoretical debates continue about the disappearance of peasantries, reality demonstrates that peasant farming is a formidable and resilient buffer for human societies, which helps stabilize, balance and enrich them.